Andean pastoral experiences and ethnographic practices - Urbano, Henrique (1985)
Following in the footsteps of his previous publications, Marzal now offers his readers a brief reflection on what he defines as syncretism, that is: "...the formation, from two religious systems that come into contact, of a , which is the product of the dialectical interaction of the elements of the two original systems (their beliefs, rites, forms of organization and ethical norms), which makes these elements persist in the new system, disappear completely, and are synthesized with similar ones of another system or are reinterpreted by a change of meanings".